A comparison of drawing and writing on facilitating word retrieval in individuals with aphasia. Issue 12 (2nd December 2019) - Hung, Pei-Fang; Ostergren, Jennifer
ABSTRACT: Background: Drawing has long been a focus in aphasia research as a compensatory strategy for improving functional communication in individuals with aphasia, but fewer studies have addressed drawing as a facilitative tool to improve their verbal output. Aims: The purpose of the current study was to investigate differences in naming accuracy in individuals with aphasia during a drawing versus a writing condition. Two research questions were formed to examine the role of drawing in facilitating naming: 1) Will participants perform better when naming with drawing compared to confrontation naming only or when naming with writing? and 2) Is the quality of the picture drawn related to the naming accuracy? Methods & Procedures: Across three separate one-hour sessions, fifteen individuals with aphasia ( n = 15) aged 44–81 years ( M = 61.47, SD  = 13.27) were evaluated using two standardized language assessments, the Western Aphasia Battery-Revised and Pyramid and Palm Tree Test, and three naming tasks designed to assess the effect of writing and drawing on naming performance. The three naming conditions consisted of confrontation naming only, naming with drawing, and naming with writing. Outcomes & Results: A one-way, repeated measures analysis of variance (ANOVA) was computed to analyze the impact of naming conditions on the participants' naming accuracy. The main effect of naming conditions was statistically significant, F (1, 14) = 5.87, p < 0.05, and Bonferroni correction revealed that the participants performed significantly better in the naming with drawing condition than with writing condition. In addition, no correlation between the quality of the pictures drawn and the participants' naming performance was found which suggested that the quality of drawing did not affect the accuracy of naming. Conclusions: When attempting to name a picture along with drawing its representation, the act of drawing may facilitate word retrieval by stimulating the semantic network associated with the word and involving the right cerebral hemisphere in the word retrieval process. Through drawing, these semantic features of the target word are more strongly activated than other related words. When the semantic features are more strongly activated, the probabilities of retrieving the target word may increase. In contrast, writing heavily relies on the left hemisphere and linguistic systems. Thus, naming when attempting to write the associated word may be a more cognitively and linguistically demanding task for individuals with aphasia.